2011
DOI: 10.1242/dev.057729
|View full text |Cite
|
Sign up to set email alerts
|

Capicua DNA-binding sites are general response elements for RTK signaling inDrosophila

Abstract: SUMMARYRTK/Ras/MAPK signaling pathways play key functions in metazoan development, but how they control expression of downstream genes is not well understood. In Drosophila, it is generally assumed that most transcriptional responses to RTK signal activation depend on binding of Ets-family proteins to specific cis-acting sites in target enhancers. Here, we show that several Drosophila RTK pathways control expression of downstream genes through common octameric elements that are binding sites for the HMGbox fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
147
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 57 publications
8
147
1
Order By: Relevance
“…Previous studies have shown that phosphorylation of Cic by ERK can result in downregulation of Cic by lowering its repressor activity, protein level, or nuclear localization (5,6,17). We hypothesized that Mnb may exert similar effects.…”
Section: Significancementioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies have shown that phosphorylation of Cic by ERK can result in downregulation of Cic by lowering its repressor activity, protein level, or nuclear localization (5,6,17). We hypothesized that Mnb may exert similar effects.…”
Section: Significancementioning
confidence: 94%
“…To assess whether Mnb could similarly affect Cic repressor activity, we used a reporter, CUASC-lacZ, which contains five GAL4 binding sites flanked on either side by two Cic binding motifs (Fig. 3A) (6). This reporter is only responsive to GAL4 in areas where Cic activity is inhibited, e.g., by RTK signaling (Fig.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Cic represses genes by binding directly to their regulatory regions and recruiting global corepressors. Both the DNA-binding domain of Cic and the Cic-binding sites within the regulatory DNA sequences are highly conserved across species (3)(4)(5). Another aspect of Cic regulation that appears to be conserved is its sensitivity to signaling by receptor tyrosine kinases (RTKs), which can antagonize gene repression by Cic (4-7) (Fig.…”
mentioning
confidence: 99%